Family Economic Resilience through Home Businesses: A Study of Young Couples in Makassar City - Andi Sadriani; Wahira Wahira (Universitas Negeri Makassar, 2025)
This study aims to analyze family economic resilience through home-based businesses among young couples in Makassar City, focusing on the type of business they run, the economic resilience strategies they implement, and the division of roles between husband and wife in managing the business and making economic decisions. The research approach used a qualitative method with a case study design. Informants were selected through a purposive sampling technique involving young couples aged 20–40 who run home-based businesses. Data were collected through in-depth interviews, direct observation, and supporting documentation such as business records and activity photos. The data analysis technique used thematic analysis through a process of data reduction, coding, categorization, and drawing out key themes relevant to the research focus. The results show that young couples run various forms of home-based businesses such as culinary, home services, and online sales that contribute significantly to family income. The economic resilience strategies implemented include income diversification, saving expenses, disciplined financial management, and utilizing social networks. In addition, the division of roles between husband and wife is carried out collaboratively and egalitarian, with decision-making carried out jointly. This study confirms that home-based businesses play a significant role in strengthening the economic resilience and stability of young families in urban areas.